2005
DOI: 10.1055/s-2005-864132
|View full text |Cite
|
Sign up to set email alerts
|

Discovering COX-Inhibiting Constituents ofMorusRoot Bark: Activity-Guided versus Computer-Aided Methods

Abstract: The aim of this study was to compare the efficiency of two well known approaches for the discovery of the bioactive principle/s in medicinal plants, namely the activity-guided isolation versus the computer-aided drug discovery by means of virtual screening (VS) techniques. Morus root bark of Morus sp. L. (Moraceae) was selected as application example for the discovery of compounds with anti-inflammatory activity. The two cyclooxygenase isoenzymes COX-1 and COX-2 were chosen as targets and the corresponding pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…However, virtual screening is based on existing knowledge of chemical plant constituents and pharmacophore models, and thus cannot fully reflect organismic complexity. By previous methods, it was difficult to avoid missing valuable compounds (Rollinger et al, 2005). Although we found that Nbenzyl-palmitamide is an active constituent of maca in osteoporosis prevention, this fact does not deny the role of other components.…”
Section: Discussionmentioning
confidence: 89%
“…However, virtual screening is based on existing knowledge of chemical plant constituents and pharmacophore models, and thus cannot fully reflect organismic complexity. By previous methods, it was difficult to avoid missing valuable compounds (Rollinger et al, 2005). Although we found that Nbenzyl-palmitamide is an active constituent of maca in osteoporosis prevention, this fact does not deny the role of other components.…”
Section: Discussionmentioning
confidence: 89%
“…This shows that natural products have a great potential as COX inhibitors. Thus, Rollinger et al [139] used a pharmacophorebased workflow for identifying novel ligands. They virtually screened the DIOS database and retrieved several compounds originating from the genus Morus.…”
Section: Cyclooxygenase (Cox) Inhibitorsmentioning
confidence: 99%
“…This resulted in the discovery of moderate COX inhibitors. For example, sanggenon E (1, Figure 5.11) gave an IC 50 value of 10.8 mM for COX-1 inhibition [139].…”
Section: Cyclooxygenase (Cox) Inhibitorsmentioning
confidence: 99%
“…[17][18][19][20] The availability of X-ray crystal structures with bound inhibitors, a large number of known active ligands, and the availability of datasets for theoretical model validation, i.e. subsets from the directory of useful decoys (DUD) database, [21] made COX-1 and -2 an ideal case study.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we deliberately include COX-1 inhibitors into this study. We aim at developing a tool for elucidating the mode-of-action of ethnopharmacologically used natural products, of which many are already known COX-1 inhibitors, e.g., [16,17,[28][29][30]. Neglecting this important anti-inflammatory mechanism would hinder the identification of anti-inflammatory compounds.…”
Section: Introductionmentioning
confidence: 99%